The Effect of the Implementation of Agricultural Extension Methods on Increasing Farmers' Capabilities - Fernanda, Dhea; Rita, Rita; Apriliyanti, Esha; Faqih, Achmad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the effect of agricultural extension methods on improving farmer capabilities in Kepuh Village, Palimanan District, Cirebon Regency. This study was conducted from June to July 2025. Farmer capabilities in this study were measured through four main indicators: agricultural insight, technical competence, decision-making ability, and attitude and independence.  The extension methods studied included direct face-to-face, field schools, demonstration plots, and digital media. This study used a quantitative approach with a census method on 50 farmers as respondents. The data analysis technique used simple linear regression preceded by validity and reliability tests, as well as classical assumption tests. The results showed that agricultural extension methods had a positive and significant effect on improving farmer capabilities. The regression equation obtained was Y = 48647.719 + 0.476X, which means that every one unit increase in the extension method will increase farmer capabilities by 0.476 units. The significance value was 0.001 (<0.05) and the coefficient of determination (R²) was 0.210. This indicates that 21% of the variation in farmer capabilities can be explained by the applied agricultural extension methods.